Rectal metastasis in a patient with long-term breast cancer: a rare case report with literature review - Lyu, Xiaohong; Mao, Feng (Frontiers in Oncology, 2026)
Gastrointestinal (GI) metastases from breast cancer are uncommon, with rectal involvement being particularly rare. Here, we present a case of a 55-year-old female with a history of bilateral breast cancer who developed rectal metastasis seven years after initial diagnosis. The patient was initially diagnosed in 2017 with left breast invasive ductal carcinoma (IDC) and right breast ductal carcinoma in situ (DCIS). Despite receiving comprehensive treatment, including modified radical mastectomy, chemotherapy, radiotherapy, and endocrine therapy, she experienced multiple metastases involving the bones, lymph nodes, and pleura. In 2024, she presented with new bowel symptoms, and colonoscopy revealed rectal wall thickening with stenosis. Biopsy confirmed metastatic breast cancer with immunohistochemistry showing GATA3(+), CDX2(-), and loss of hormone receptor expression compared to the primary tumor. This case underscores the importance of considering gastrointestinal metastasis in breast cancer patients with bowel symptoms, even years after initial treatment. We also review the literature regarding the literature on the diagnosis, treatment, and prognosis of breast cancer rectal metastasis.